ANALISIS DETERMINAN RASIO MODAL BANK BUMN DI INDONESIA - Saifullah Saputra (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2016)
Capital aspect is the one very important aspect  in the banking sector,not only for business developing but also  to overcome the  various of risk. Inorder to keep the healty and stability of the state owned bank capital, the centralbank as monetary authority in Indonesia has determine the regulation aboutcapital healty. It looks from the minimum capital requirement that must beenobeyed by banking is 8%. This situation based on economy crisis case in 1997which has an impact on the banking sector. This study aims to analyze the effectof profitability, credit risk, efficiency, liquidity, exchange rate and inflation oncapital ratios of state owned bank in Indonesia. The type of this research aredescriptive and associative using time series data from the first quarter of 2004until the fourth quarter of 2015 with documentation data collected technique.Data were analyzed with multiple linear regression model, the prerequisite test(multicolinearity, autocorrelation and heteroscedasticity), t test, and F test. The result shows that (1) Profitability has positive and significant effect oncapital ratios of state owned bank in Indonesia. (2) Credit risk has positive andsignificant effect on capital ratios of state owned bank in Indonesia. (3)Efficiency has negative and significant effect on capital ratios of state ownedbank in Indonesia.  (4) Liquidity has negative and significant effect on capitalratios of state owned bank in Indonesia. (5) Exchange rate has positive andsignificant effect on capital ratios of state owned bank in Indonesia. (6) Inflationhas positive and not significant effect on capital ratios of state owned bank inIndonesia.